Advance in the Correlation between Diabetic Nephropathy and Abnormal Serum Thyroid Hormone Levels in Patients - Zhiqiu Liu (Emergency Medicine International)
This study was developed to explore the correlation between diabetic nephropathy (DN) and abnormal serum thyroid hormone (TH) levels in patients, which can provide a reference for disease prevention and control in patients with DN. DN is the most serious complication of diabetes. The mortality rate of diabetic patients with DN is approximately 30 times higher than that of diabetic patients without DN. DN leads to high blood sugar, which causes vascular dysfunction in patients, causes cardiovascular disease, aggravates the disease and disease complexity, and thus increases the mortality of patients. DN patients often have oxidative stress and even fibrosis in severe cases. TH has a potential renal protective effect and can also regulate glucose metabolism and improve abnormal glucose tolerance and insulin resistance. Abnormal serum TH levels increase the risk of DN. Normal thyroid function plays an important role in regulating the physiological functions of the human body. Hormonal disorders promote the development of diabetes mellitus (DM) into DN. The pathogenesis, clinical manifestations, detection, and treatment methods of DN were reviewed in this study. The research progress of the influence of TH on DN was analyzed. This study is conducive to clinical research on DN and provides a reference.